2015
DOI: 10.1016/j.chemosphere.2014.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad in the native stingless bee Melipona quadrifasciata: Regrettable non-target toxicity of a bioinsecticide

Abstract: The risks imposed by novel insecticides, mainly bioinsecticides, are largely unknown despite their increased use and their perceived environmental safety, which is based on their natural origin. Furthermore, unlike honeybees, native pollinator species have received little attention. In the present study, the lethal and sublethal effects of the neonicotinoid imidacloprid and the bioinsecticide spinosad were assessed in the stingless bee species Meliponaquadrifasciata, an important native pollinator in the Neotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 52 publications
3
60
0
3
Order By: Relevance
“…Because changes in the function of nervous tissue can affect basic autonomic processes such as thermoregulation or respiration (Sláma & Miller, 1987; Kestler, 1991; Belzunces, Tchamitchian & Brunet, 2012; Hatjina et al, 2013; Karise & Mänd, 2015), we measured the metabolic rates of adult bees on the day of emergence. Relatively little is known about the effects of developmental pesticide exposure on adult insect metabolic rates, but acute exposure has been found to alter respiratory rhythms, particularly the propensity to engage in discontinuous gas exchange (Zafeiridou & Theophilidis, 2004; Hatjina et al, 2013; Tomé et al, 2015). We found that while the majority of bees engaged in discontinuous patterns of CO 2 release, a small proportion of bees breathed continuously throughout the observation period, but this propensity was not affected by clothianidin exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because changes in the function of nervous tissue can affect basic autonomic processes such as thermoregulation or respiration (Sláma & Miller, 1987; Kestler, 1991; Belzunces, Tchamitchian & Brunet, 2012; Hatjina et al, 2013; Karise & Mänd, 2015), we measured the metabolic rates of adult bees on the day of emergence. Relatively little is known about the effects of developmental pesticide exposure on adult insect metabolic rates, but acute exposure has been found to alter respiratory rhythms, particularly the propensity to engage in discontinuous gas exchange (Zafeiridou & Theophilidis, 2004; Hatjina et al, 2013; Tomé et al, 2015). We found that while the majority of bees engaged in discontinuous patterns of CO 2 release, a small proportion of bees breathed continuously throughout the observation period, but this propensity was not affected by clothianidin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Across a diversity of insects, exposure to neuro-active pesticides has been show to affect rates and patterns of gas exchange, such as the propensity to engage in discontinuous gas exchange (reviewed in Karise & Mänd, 2015). In bees, acute exposure to imidacloprid has been shown to alter abdominal ventilation patterns in adult honey bees (Hatjina et al, 2013) and to increase metabolic rates in the stingless bee Melipona quadrifasciata (Tomé et al, 2015). Accordingly, patterns of respiratory gas exchange are considered a useful physiological measure of an insects’ response to stress, therefore we used flow-through respirometry to examine the metabolic rate and respirometry rhythms of adult O. bicornis exposed to clothianidin as larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Both neonicotinoids and formamidines mimic the action of biogenic amines (Evans and Gee 1980;Matsuda et al 2001). Consequently, the chronic exposure of bees to sublethal doses of these substances may lead to critical modifications of neural signalling and, eventually, cause behavioural dysfunctions (Farooqui 2013), such as a reduction of respiration rate and flight activity (M. quadrifasciata : Tomé et al 2015), an impairment of olfactory learning and memory, or a decreasing gustatory responsiveness (A. mellifera : Mengoni Goñalons and Farina 2015). Given these interactions between pesticides, biogenic amine signalling, and bee behaviour, the results of our study provide an important baseline for future studies on this topic in stingless bees.…”
Section: Discussionmentioning
confidence: 99%
“…Muitos desses ingredientes ativos, durante sua rota metabólica, afetam diferentes processos celulares que impactam a longevidade, o comportamento e a fisiologia do inseto, e podem causar efeitos individuais e consequências para a colônia ao longo do tempo. Os dados mostram que eles podem afetar o processamento das informações no cérebro de S. postica e Melipona quadrifasciata Tomé et al, 2015). Há dados, inclusive, que mostram que produtos classificados como biopesticidas, como a azadiractina, podem causar deformações nas larvas e causar impactos sobre a manutenção do número de indivíduos da colônia .…”
Section: O Uso De Agrotóxicos Na Agriculturaunclassified